High sensitivity troponins: A potential biomarkers of cardiovascular risk for primary prevention - Leite, Luis; Matos, Pedro; Leon-Justel, Antonio; Espírito-Santo, Claudio; Rodríguez-Padial, Luis; Rodrigues, Fernando; Orozco, Domingo; Redon, Josep (Frontiers in Cardiovascular Medicine, 2022)
There have been several approaches to building charts for CV risk, all of which have both strengths and limitations. Identifying early organ damage provides relevant information and should be included in risk charts, although the direct relationship with risk is imprecise, variability between operators at the time to assess, and low availability in some healthcare systems, limits its use. Biomarkers, like troponin (cTns) isoforms cTnI and cTnT, a cardiac specific myocyte injury marker, have the great advantage of being relatively reproducible, more readily accessible, and applicable to different populations. New and improved troponin assays have good analytical performance, can measure very low levels of circulating troponin, and have low intra individual variation, below 10 %. Several studies have analyzed the blood levels in healthy subjects and their predictive value for cardiovascular events in observational, prospective and post-hoc studies. All of them offered relevant information and shown that high sensitivity hs-cTnI has a place as an additional clinical marker to add to current charts, and it also reflects sex- and age-dependent differences. Although few more questions need to be answered before recommend cTnI for assessing CV risk in primary prevention, seems to be a potential strong marker to complement CV risk charts.